Philippine Computable General Equilibrium Model (PCGEM) - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2000)
This paper discusses the structure of the Philippine computable general equilibrium model (PCGEM). The model is a medium-sized CGE model of the Philippine economy. It disaggregates the production sector into 34 sectors. It incorporates 3 types of factor inputs; labor, variable capital and capital. The household sector is grouped in decile. Production differentiation is introduced in imports and exports. PCGEM is a neoclassical CGE model, with price clearing mechanisms. Furthermore, it is a full employment model. At its present state, the model is closed with fixed current account balance, fixed exchange rate (the numeriare), and endogenous PINDEX, which is the weighted value added price (or the GDP deflator). Also, savings go back into the system in the form of investments. The model is static and calibrated using the 1990 social accounting matrix and the 1990 sectoral tariff revenue. PCGEM is coded in a software called General Algebraic Modelling System (GAMS).
Keywords: 330; economic/development modelling; Allgemeines Gleichgewicht; Volkswirtschaft; Philippinen